The Autumn Springs Retirement Home massacre - Fracassi, Philip, 1970- (Tor Publishing Group, 2025)
"Brimming with dark humor, violence, and mystery, The Autumn Springs Retirement Home Massacre is a blood-soaked slasher sure to keep readers guessing until the very last page. Rose DuBois is not your average final girl. Rose is in her late 70s, living out her golden years at the Autumn Springs Retirement Home. When one of her friends dies alone in her apartment, Rose isn't too concerned. Accidents happen, especially at this age! Then another resident drops dead. And another. With bodies stacking up, Rose can't help but wonder: are these accidents? Old age? Or something far more sinister? Together with her best friend Miller, Rose begins to investigate. The further she digs, the more convinced she becomes: there's a killer on the loose at Autumn Springs, and if she isn't careful, Rose may be their next victim."-- Provided by publisher.